New technologies for safe practice and training during pregnancy: a gynecologist and forensic pathologist perspective narrative review - Capasso, Emanuele; Marisei, Mariagrazia; Aquino, Carmen Imma; Di Lorenzo, Pierpaolo; Casella, Claudia (Frontiers in Surgery, 2025)
This paper investigates the intersection of gender health equity within two distinct medical residency programs: obstetrics &gynecology and forensic pathology. It specifically addresses the unique challenges that young female residents encounter during pregnancy, emphasizing the Italian regulatory frameworks and recommendations pertinent to both fields. The online search for this narrative review was based on keywords such as: “medicine” AND “education” AND “pregnancy” on the main online scientific database along with “metaverse” AND “education” AND “pregnancy”. The analysis reveals the heightened risks faced by female medical doctors in surgical and forensic environments, underlining the need for targeted support. Additionally, this study explores the perceived potential of augmented reality (AR) and the metaverse as innovative solutions to mitigate biological risks, thereby enabling pregnant surgeons to maintain effective practice during this critical period. The findings obtained from a literature review aim to contribute to ongoing discussions about improving gender equity in medical training and practice, regarding the surgical and forensic field where the temporary stopping period may result in a different surgical learning curve compared to that of male colleagues.